1982
DOI: 10.1126/science.6173921
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight of Human Gamma Interferon Is Similar to that of Other Human Interferons

Abstract: The molecular weight (as determined by molecular sieve chromatography) of human gamma interferon, formerly referred to as immune or type II interferon, is between 40,000 and 70,000. On sodium dodecyl sulfate-polyacrylamide gel electrophoresis, gamma interferon activity was recovered mainly from two regions of the gels corresponding to molecular weights of 20,000 and 25,000. The results suggest that in native form human gamma interferon may be aggregated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Another factor that contributed to the successful purification of IFN-y described in this paper was the recent demonstration that the biological activity of human IFN-y was not completely destroyed by treatment with NaDodSO4 (8). Residual biological activity after NaDodSO4 treatment could thus be used as a marker for the identification of IFN-y proteins under conditions precluding noncovalent interactions among protein molecules.…”
mentioning
confidence: 88%
“…Another factor that contributed to the successful purification of IFN-y described in this paper was the recent demonstration that the biological activity of human IFN-y was not completely destroyed by treatment with NaDodSO4 (8). Residual biological activity after NaDodSO4 treatment could thus be used as a marker for the identification of IFN-y proteins under conditions precluding noncovalent interactions among protein molecules.…”
mentioning
confidence: 88%
“…Purified recombinant interferon alpha A was the immunogen for preparation of the antibody to interferon alpha. After a three-step purification process (21), the interferon gamma used to prepare the latter antibody was virtually free of interleukin 1 Phenotyping of PBMC. No patient's PBMC spontaneously produced interferon gamma at either bleed.…”
Section: Methodsmentioning
confidence: 99%
“…were kindly provided by Sydney Pestka (Nutley, NJ) and Jan Vilcek (New York), respectively (20,21). Purified recombinant interferon alpha A was the immunogen for preparation of the antibody to interferon alpha.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has been shown that IFN-y molecule produced by mitogen-stimulated T lymphocytes undergoes glycosylation (26), and a number of investigators have shown that mouse IFN-y derived from normal spleen cells stimulated with mitogens displays a broad charge heterogeneity and different degrees of glycosylation and hydrophobicity (26,30,31). Similar findings have also been reported for the human IFN-y by Yip et al (10,32). In particular, they found that IFN--y activity recovered from a partially purified preparation of human IFN-y run on NaDodSO4/PAGE corresponded to two bands with molecular weights of 21 and 25 kDa.…”
Section: Discussionmentioning
confidence: 56%